2014
DOI: 10.1039/c4cc03936j
|View full text |Cite
|
Sign up to set email alerts
|

A bistable switch in pH in urease-loaded alginate beads

Abstract: A bistable switch from a low pH (unreacted "off") state to a high pH (reacted "on") state was obtained in enzyme-loaded gel beads in response to supra-threshold substrate concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
(21 reference statements)
2
24
0
Order By: Relevance
“…However, we can compare with earlier studies of the clock reaction performed with the enzyme immobilized in alginate beads. In this case although the beads displayed initially high activity, this was found to decrease over the over the course of hours [17]. Using a fixed mass of thiol-acrylate beads in a solution of urea and acid we found that the enzyme-loaded beads were able to produce pH clock reactions similar to those obtained in the solution phase experiments.…”
Section: Discussionsupporting
confidence: 48%
“…However, we can compare with earlier studies of the clock reaction performed with the enzyme immobilized in alginate beads. In this case although the beads displayed initially high activity, this was found to decrease over the over the course of hours [17]. Using a fixed mass of thiol-acrylate beads in a solution of urea and acid we found that the enzyme-loaded beads were able to produce pH clock reactions similar to those obtained in the solution phase experiments.…”
Section: Discussionsupporting
confidence: 48%
“…In an attempt to mimic cellular functions, chemists and bio‐engineers have synthesized and analyzed molecular networks operating far from equilibrium, driven by non‐linear reactions that induce positive or negative (inhibiting) feedback . While bistable and oscillatory behavior has been demonstrated and studied extensively using (bio)chemical networks, the target of the current paper, multistationarity – where systems possess multiple resting states as seen often in biology – has rarely been addressed …”
Section: Introductionmentioning
confidence: 99%
“…[1] In an attempt to mimic cellular functions, chemists and bio-engineers have synthesized and analyzed molecular networks operating far from equilibrium, driven by non-linear reactions that induce positive or negative (inhibiting) feedback. [2,3] While bistable [4][5][6][7][8] and oscillatory [8][9][10] behavior has been demonstrated and studied extensively using (bio)chemical networks, the target of the current paper, multistationaritywhere systems possess multiple resting states as seen often in biology [11][12][13][14] -has rarely been addressed. [15][16][17] Recent advances in Systems Chemistry have generated new platforms for studying simple networks operating far from equilibrium, [18][19][20][21][22][23][24][25] including cooperative and competing cyclic network models such as hypercycles and autocatalytic sets.…”
Section: Introductionmentioning
confidence: 99%
“…One of the simplest systems to realize this is the urease-catalyzed hydrolysis of urea, which displays autocatalysis driven by the increase in pH accompanying the production of ammonia under non-buffered conditions. [1][2][3][4] The transient pH jump in the clock reaction can be coupled to self-assembling systems operating in the targeted pH regime, where upon they form and decay on a pre-programmed course in closed systems as encoded by the pH prole. Heuser et al 5 coupled this transient state with dipeptides and created an autonomously self-regulating dynamic gel with programmed lifetime.…”
Section: Introductionmentioning
confidence: 99%